A review of a management experience of the Peruvian Society of Obstetrics and Gynecology (SPOG) - Romero, José Pacheco (2023)
Medical societies usually have as their mission and vision the improvement of theirmembers' competencies and therefore academic activities are usually the mostimportant objective. The Sociedad Peruana de Obstetricia y Ginecología (SPOG) is anacademic institution, but it has become a reference for women's health and is part ofthe Advisory Group of the Ministry of Health; it promotes and defends public policiesfor the benefit of sexual and reproductive health, recently promoting the vaccinationof pregnant women against COVID-19 and reducing maternal deaths. In 2023, SPOGdefends women's right to emergency contraception before the Constitutional Courtand therapeutic abortion before the Supreme Court of Justice. In addition, thePeruvian Journal of Gynecology and Obstetrics (RPGO, for its acronym in Spanish)has been published since 1955 and with the support of the different SPOG boardshas recently been indexed in Scopus. In reviewing the latest Strategic Plan 2022-2026,SPOG can be considered a modern academic society that seeks to be self-sustainablethrough the implementation of projects with external cooperation and with thesupport of the associates and a modern transparent and efficient administration.Current and future medical societies not only conduct the scientific academic activityof their specialty but also participate in public health policies in the area of theircompetence.